The intestinal microbiome and Cetobacterium somerae inhibit viral infection through TLR2-type I IFN signaling axis in zebrafish - Hui Liang; Ming Li; Jie Chen; Wenhao Zhou; Dongmei Xia; Qianwen Ding; Yalin Yang; Zhen Zhang; Chao Ran; Zhigang Zhou (Microbiome)
Abstract Background Evidence has accumulated to demonstrate that intestinal microbiome can inhibit viral infection. However, our knowledge of the signaling pathways and identity of specific commensal microbes that mediate the antiviral response is limited. Zebrafish have emerged as a powerful animal model for study of vertebrate-microbiota interactions. Here, a rhabdoviral infection model in zebrafish allows us to investigate the modes of action of microbiome-mediated antiviral effect. Results We observed that oral antibiotics-treated and germ-free zebrafish exhibited greater spring viremia of carp virus (SVCV) infection. Mechanistically, depletion of the intestinal microbiome alters TLR2-Myd88 signaling and blunts neutrophil response and type I interferon (IFN) antiviral innate immunity. Through 16S rRNA sequencing of the intestinal contents from control and antibiotic(s)-treated fish, we identified a single commensal bacterial species, Cetobacterium somerae, that can restore the TLR2- and neutrophil-dependent type I IFN response to restrict SVCV infection in gnotobiotic zebrafish. Furthermore, we found that C. somerae exopolysaccharides (CsEPS) was the effector molecule that engaged TLR2 to mediate the type I IFN-dependent antiviral function. Conclusions Together, our results suggest a conserved role of intestinal microbiome in regulating type I IFN antiviral response among vertebrates and reveal that the intestinal microbiome inhibits viral infection through a CsEPS-TLR2-type I IFN signaling axis in zebrafish. Video Abstract